Non-conventional vortex configurations in a mesoscopic flat disk - Barba-Ortega, J.; Sardella, Edson [UNESP]; Albino Aguiar, J.; Peeters, F. M. (Elsevier, 2013)
The influence of superficial defects on the vortex configurations of a thin superconducting disk is investigated within the time dependent Ginzburg-Landau formalism. The free energy, magnetization, vorticity, and the Cooper pair density are calculated for both metastable and stable vortex configurations and different number of defects on its surface in the presence of an external magnetic field applied perpendicular to the disk area. We show that the competition between the confinement geometry and the geometric position of the defects leads to non-conventional vortex configurations which are not compatible with the symmetry of the sample geometry.
Keywords: Ginzburg-Landau; Mesoscopic samples; Vortex; Cooper-pair density; External magnetic field; Ginzburg-Landau formalism; Mesoscopics; Superconducting disks; Superficial defects; Vortex configurations; Superconducting materials; Surface defects; Vortex flow